2001
DOI: 10.1136/tc.10.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Why does smoking so often produce dependence? A somewhat different view

Abstract: The usual explanation for why smoking produces dependence focuses on the eVects of nicotine on dopamine and other neurobiological explanations. This review oVers four somewhat diVerent explanations: (1) nicotine can oVer several psychopharmacological benefits at the age when such benefits are especially needed; (2) cigarettes provide for a rapid, frequent, reliable and easy-to-obtain reward; (3) nicotine is not intoxicating, allowing chronic intake; and (4) the long duration of the nicotine withdrawal syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 26 publications
(14 reference statements)
1
24
0
1
Order By: Relevance
“…The same author stated that smokers with a high degree of dependence can also present with low motivation due to their lack of confidence in their ability to succeed; they believe they are incapable of quitting and are afraid of suffering from withdrawal syndrome, since their previous attempts have been unsuccessful. (25) We found a significant correlation between the degree of nicotine dependence and probable depression. Among the elderly individuals whose Geriatric Depression Scale scores were indicative together with depression, less social and medical pressure to stop smoking, fewer opportunities, low self-efficacy and lack of productive activity can reinforce the smoking habit.…”
Section: Discussionmentioning
confidence: 58%
“…The same author stated that smokers with a high degree of dependence can also present with low motivation due to their lack of confidence in their ability to succeed; they believe they are incapable of quitting and are afraid of suffering from withdrawal syndrome, since their previous attempts have been unsuccessful. (25) We found a significant correlation between the degree of nicotine dependence and probable depression. Among the elderly individuals whose Geriatric Depression Scale scores were indicative together with depression, less social and medical pressure to stop smoking, fewer opportunities, low self-efficacy and lack of productive activity can reinforce the smoking habit.…”
Section: Discussionmentioning
confidence: 58%
“…It has been suggested that smokers who experience chronic, low-grade withdrawal are more likely to relapse than those whose symptoms abate quickly (Hughes, 2001), underscoring the important role that duration plays in predicting relapse. Few studies have examined physiological correlates of intermediate to longterm withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…(194) Smokers who consume a large quantity of cigarettes can also present low motivation due to their lack of confidence to succeed. They believe they are incapable and are afraid of suffering from withdrawal syndrome, since they have already tried and failed before.…”
Section: Low Motivationmentioning
confidence: 99%
“…They believe they are incapable and are afraid of suffering from withdrawal syndrome, since they have already tried and failed before. (194) The principal strategies to overcome low motivation are discussed in the "Evaluation of the motivation level" section of these guidelines. the physician to practice the art of care until they achieve total abstinence.…”
Section: Low Motivationmentioning
confidence: 99%